(untitled) (Development Service Industry Management, 2024)
In modern conditions one of the most important aspects ensuring the effective functioning of enterprises in the trade and entertainment sphere, as well the formation of positive results its financial activity, is the existence of an effective marketing strategy that will ensure a high level of development and protect business from threats. Protection is due to the ability of management bodies of shopping and entertainment complexes at the appropriate levels: to ensure the implementation of marketing strategies; to neutralize the negative impact of crisis phenomena on business structures; to form an adequate accounting system of financial flows and to strengthen the operational efficiency of the control system in process of comprehensive planning the marketing strateg etc. Modern scientific studies point to the fact that without a unified marketing system of enterprises in the trade and entertainment sphere it is impossible to achieve a high level of financial performance and ensure security, stabilize the economic situation and create an effective mechanism for conducting business. Formation of marketing strategies is one of the most essential and difficult stages of the marketing process. After all, the marketing strategy is the basis of the company’s actions in specific market conditions, which determines the methods of applying marketing in order to expand target markets in order to achieve effective results. It has been established that the main purpose of the marketing strategy of the shopping and entertainment complex is to coordinate the company’s marketing goals with its capabilities, consumer requirements, to use the weak positions of competitors and their competitive advantages. The marketing strategy is subordinated to the corporate strategy of the firm. In its form, the strategy is one of the management documents, which can be presented in the form of graphs, tables, diagrams, etc., although in its content, the strategy is a set of actions to achieve the organization’s goals. Complex economic conditions, changes in technology and technology, and growing consumer demands force shopping and entertainment complexes to apply marketing strategies to effectively fight in today’s complex business world. It is proved that there are three global directions of the marketing strategy of the trade and entertainment complex, which are used in practical activities, namely: segmentation, diversification and internationalization.